RESPON PERTUMBUHAN BEBERAPAxVARIETAS TANAMAN KACANGxPANJANGx(Vignaxsinensis L.) DENGANxBERBAGAI MACAM MULSA - Kholid Ashari; Pramono Hadi, Srie Juli Rachmawatie (PROSEDING, 2022)
Thisxresearchxwasxconductedxto determine the response growthxof several varieties of long beans (Vigna sinensis L.) with several kinds of mulch. Thisxresearchxwas conducted inxAprilx2019 until July 2019,xin the Sumberejo Village, Ngablak District, MagelangxRegencyxatxanxaltitude of 1,370 mxabovexseaxlevel.xThisxresearchxuses factorialxmethodexwithxSplitplotxDesign patternxwhichxconsistsxofxtwoxtreatmentxfactors. Thexfirstxtreatmentxfactorxisxvarietyx(V)xconsisting of 3 levels (V1 = cash tavi, V2 = pertiwixand V3 = tavi parade). The secondxtreatment factor, mulch type (M) consisting of 3 types (M0 = no mulch, M1 =xstraw mulchxand M2 = silver black plastic mulch). Dataxanalysis using variancexwithxF test atx5% andx1% levelsxand ifxthe threextreatments were significantly different followed byxDuncan'sxmultiplexrangextest at 5% level. The resultsxofxthisxstudyxindicatexthat: The treatmentxof several varieties of long beans (V) which is the bestxgrowthxandxyieldxofxplantsxis tavi cash varieties.xThe best type of mulch (M) treatmentxonxthexgrowthxandxyieldxofxlongxbeanxplants is M2 (silver black plastic mulch) because thexusexofxsilverxplasticxmulchxcan reflect mostxof the sunlight received, and this will increase the absorption of light used for photosynthesis . In the interaction of several varieties of long beans with mulch (V x M), the highest unity was obtained in the combination of V1M2 (2,54 kg), the highest weight per pod was V1M2 (8,23), at the best flowering age was obtained at the combination of V1M2 treatment ( 36 HST), the highest pod length of V3M0 (61,55 cm)xandxthexhighestxnumber ofxpods perxplantxin the V3M2 treatmentxcombination (4,82). Keywords: varieties, mulch, long beans, straw